METAPHYSICS OF LONELINESS - Markova, Ilinida (E-Journal VFU, 2024)
Escape from loneliness is like escape from freedom - sought after, desired, enslaving, yet accompanied by the expectation of salvation and happiness - accompanying illusory living. Man will always fear and obey conventional notions of the meaning of everything. His self-love will always prevent him from being alone with himself. Truth will always be accessible only in moments of solitude - when self-deception is not possible.